A 0.8–6 GHz Wideband Receiver Front-End for Software-Defined Radio. (9th December 2013) - Lin, Kuan-Ting; Wang, Tao; Lu, Shey-Shi
Abstract : A wideband (0.8–6 GHz) receiver front-end (RFE) utilizing a shunt resistive feedback low-noise amplifier (LNA) and a micromixer is realized in 90 nm CMOS technology for software-defined radio (SDR) applications. With the shunt resistive feedback and series inductive peaking, the proposed LNA is able to achieve a wideband frequency response in input matching, power gain and noise figure (NF). A micromixer down converts the radio signal and performs single-to-differential transition. Measurements show the conversion gain higher than 17 dB and input matching (S11) better than −7.3 dB from 0.8 to 6 GHz. The IIP3 ranges from −7 to −10 dBm, and the NF from 4.5 to 5.9 dB. This wideband receiver occupies 0.48 mm 2 and consumes 13 mW.